Development of radial aerodynamic swirlers - Mohd. Jaafar, Mohammad Nazri (Faculty of Mechanical Engineering, 1997)
Experimental studies show that swirl has large-scale effects on flowfields: jet growth, entrainment and decay (for isothermal flows) and flame size, shape, stability and combustion intensity (for combustion flows) are affected by the degree of swirl imparted to the flow. This degree of swirl is usually characterises by the momentum to the axial flux of axial momentum times the equivalent nozzle radius. This parameter, denoted by the symbol S, is called the swirl number and has been used extensively to designate the strength of the swirl. This paper is to review the aerodynamics of swirling flow in combustion system.